Mathematical modeling of weight loss and crust temperature of toast bread containing guar gum during baking process - Mohammadi Golchin, Farnaz (Food Sci Nutr, 2020)
Baking is a combined process in which several interconnected chemical, biochemical, and physical phenomena such as starch gelatinization and formation of porous structures occur. These changes affect the ultimate quality of the product such as taste. In this study, effects of guar gum (at 1% level) and baking temperature (at 190, 200, 210, 220, and 230°C) on crust temperature and weight loss of toast bread samples during 40 min exposure were investigated. According to the results, raising the oven's temperature from 190°C to 230°C will rise the crust's temperature of toast bread samples both in the control group (from 128.5°C to 190.2°C) and test group (from 120.18°C to 164.8°C), as well as the percentage of weight loss in toast bread samples both in the control group (from 35.11% to 47.23%) and test group (from 20.37% to 29.57%). We also worked with polynomial functions, exponential functions, fractional functions, Gaussian functions, and MATLAB to model the percentage of weight loss and an increase in the crust temperature of toast bread samples during the baking process. And ultimately, the correlation coefficients of the models were calculated and compared to analyze the results of predictor functions.